(untitled) (AYUSHDHARA, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders of childhood, characterised by inattention, impulsivity, and hyperactivity, which significantly affect academic, social, and emotional functioning. The etiology of ADHD is multifactorial, involving an interplay of neurobiological, environmental, and genetic determinants. If left untreated, ADHD can hampers learning ability, self-regulation, and behavioural development, leading to long-term challenges in adulthood. Ayurveda provides a comprehensive approach to such cognitive and behavioural disorders. Brahmyadi Yoga, a classical polyherbal formulation, contains Brahmi, Shankhapushpi, Vacha, Kushmanda with Kushta and Madhu which are well known for their Medhya Rasayana (nootropic and cognitive-enhancing) properties. Its bioactive phytoconstituents exert neuroprotective, adaptogenic, and nootropic effects, supporting brain plasticity, neurotransmitter modulation, and impulse regulation. By reducing hyperactivity, improving concentration, and enhancing cognitive functions, Brahmyadi Yoga offers a safe and holistic therapeutic option for managing ADHD in children.